2000
DOI: 10.1038/sj.bjp.0703005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine and chlorisondamine on cerebral glucose utilization in immobilized and freely‐moving rats

Abstract: 1 Chlorisondamine blocks central nicotinic receptors for many weeks via an unknown mechanism. Intracerebroventricular administration of [ 3 H]-chlorisondamine in rats results in an anatomically restricted and persistent intracellular accumulation of radioactivity. The initial aim of the present study was to test whether nicotinic receptor antagonism by chlorisondamine is also anatomically restricted. 2 Male adult rats were pretreated several times with nicotine to avoid the disruptive eects of the drug seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…The central blockade by chlorisondamine has a longer duration of action in the rat than was observed for pigeons (Clarke, 1984;Decker et al, 1994;el-Bizri & Clarke, 1994;Marenco et al, 2000;Reuben et al, 1998). The difference in duration of chlorisondamine's blockade between the rat and pigeon may be related to many factors including route of chlorisondamine administration (intramuscularly vs. icv) and species differences, such as overall metabolic rate, metabolism of nicotine, and the subtypes of central nicotinic receptors.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The central blockade by chlorisondamine has a longer duration of action in the rat than was observed for pigeons (Clarke, 1984;Decker et al, 1994;el-Bizri & Clarke, 1994;Marenco et al, 2000;Reuben et al, 1998). The difference in duration of chlorisondamine's blockade between the rat and pigeon may be related to many factors including route of chlorisondamine administration (intramuscularly vs. icv) and species differences, such as overall metabolic rate, metabolism of nicotine, and the subtypes of central nicotinic receptors.…”
Section: Discussionmentioning
confidence: 55%
“…Another method of tracing alterations of functional activity in the brain is the measurement of local metabolic rates using local cerebral glucose utilization (LCGU). Using this method, Marenco et al (2000) mapped central nicotinic effects in the rat and the ability of chlorisondamine to block the central effects of nicotine. Marenco et al (2000) observed that chlorisondamine, administered intracerebroventricularly (icv) 4 weeks prior to nicotine, attenuated the nicotine-induced decrease in LCGU in several brain loci in the rat, including the nucleus accumbens, hippocampus, and intermediate habenula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A bolus of nicotine given in the general circulation produces both localized dopaminergic activation (e.g., Champtiaux et al 2003;Marubio et al 2003;Maskos et al 2005;Mameli-Engvall et al 2006) and distributed effects such as the release of other neurotransmitters, the synthesis of transcription factors (Hiremagalur and Sabban 1995;Fu et al 2003;Rossi et al 2005), the consumption of glucose (London et al 1988;Marenco et al 2000) showing a nicotine-evoked stimulation of neural activation, and brain metabolism. However, the nicotine-stimulating effect is exerted both by β2*nAChRs and α7 subtypes expressed on GABAergic neurons and glutamatergic nerve endings, but also and mostly at nonsynaptic compartments, and can increase the influx of both Na+ and Ca2+ (Pakkanen et al 2005).…”
Section: Discussionmentioning
confidence: 99%